2020
DOI: 10.1016/s2213-2600(20)30190-9
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily, single-inhaler mometasone–indacaterol–glycopyrronium versus mometasone–indacaterol or twice-daily fluticasone–salmeterol in patients with inadequately controlled asthma (IRIDIUM): a randomised, double-blind, controlled phase 3 study

Abstract: Once-daily, single-inhaler mometasone-indacaterol-glycopyrronium versus mometasoneindacaterol or twice-daily fluticasone-salmeterol in patients with inadequately controlled asthma (IRIDIUM) IRIDIUM trial investigators; Kerstjens, Huib A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(192 citation statements)
references
References 27 publications
8
179
0
5
Order By: Relevance
“…This is a post hoc analysis of data from the IRIDIUM study 14 in patients from Asian countries (Japan, China, Philippines, Vietnam and Thailand). IRIDIUM was a 52-week, randomised, double-blind, double-dummy, parallel-group, active-controlled study ( ClinicalTrials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a post hoc analysis of data from the IRIDIUM study 14 in patients from Asian countries (Japan, China, Philippines, Vietnam and Thailand). IRIDIUM was a 52-week, randomised, double-blind, double-dummy, parallel-group, active-controlled study ( ClinicalTrials.…”
Section: Methodsmentioning
confidence: 99%
“…9 10 Similar to the Global Initiative for Asthma report, 5 the Japanese asthma guidelines 6 and Korean asthma guidelines 7 also recommend treatment with add-on long-acting muscarinic antagonist (LAMA, tiotropium) in patients with uncontrolled asthma with LABA/ICS therapy. The addition of LAMA to LABA/ICS has demonstrated improvement in lung function, asthma control and exacerbation reduction, with fewer non-serious adverse events, overall, [11][12][13][14] as well as in the Asian population 15 with uncontrolled asthma.…”
Section: Why Read On?mentioning
confidence: 99%
See 1 more Smart Citation
“…The observed differences were small in magnitude and were not considered clinically relevant in view of the observed exposure variability, challenges with characterizing C max for inhaled drugs and the available safety data at doses higher than proposed doses of IND [25], GLY [26] and MF [27] as part of IND/GLY/MF. In the Phase 3 clinical study for IND/GLY/MF in asthma patients [28], while the study was not powered to demonstrate differences by subgroups, there were no observed differences in clinical efficacy or safety profile according to recorded ethnicity. In addition, during the development of IND/GLY/MF in Japan, 52 weeks treatment of IND/GLY/MF was well tolerated in Japanese patients with inadequately controlled asthma [29].…”
Section: Table 4 Summary Of the Exploratory Analysis Of Plasma Mf Pk mentioning
confidence: 99%
“…published, showing that different ICS/LABA/LAMA combinations can improve lung function and symptoms in patients with moderate or severe asthma who remain uncontrolled with ICS/LABA. [68][69][70] High ICS doses would be only prescribed in "T2-high" patients who have failed prior therapeutic attempts. Consequently, biologic therapy would be restricted to those asthmatics who remain uncontrolled with high-dose ICS triple therapy if they express biomarkers indicative of "T2-high" inflammatory response.…”
mentioning
confidence: 99%